Valuing Florida Water Resources: Households’ Willingness to Pay for Water Availability: FE1068, 8/2019 - Borisova, Tatiana; He, Fei; Bi, Xiang; Grogan, Kelly; Wade, Tara; Shah, Syed (EDIS, 2019)
This paper is a part of the EDIS series “Economic Value of Florida Water Resources”. As the other papers in the series discuss, water resources provide us with a variety of goods and services (often referred to as ecosystem services). This paper discusses another ecosystem service that Florida water resources provide: water supply for households needs. In this article, we present several examples of valuing water availability found in literature and focused on Florida and other regions.